Pharmacological and analytical aspects of withaferin A: A concise report of current scientific literature - Patel K.; Singh R.B.; Patel D.K. (My University, 2025)
Withaferin A is an important phytoconstituents of Withania somnifera (W. Somnifera) belonging to the category of withanolides, that are a group of naturally occurring C28-steroidal lactone triterpenoids. Withaferin A has been used in the traditional and indigenous system of medicine for the treatment of various disorders. In view of its unique therapeutic potential, it has gained much attention in the modern science. In the couple of the years, Withaferin A has been scientifically validated for different pharmacological activities including anti-cancer, adaptogenic, anti-stress, anti-convulsant, immunomodulatory, neurological, anti-inflammatory, anti-tumor, cardioprotective, and neuroprotective activities. Pharmacological and analytical aspects of Withaferin A were highlighted in the present article. From the literature review it was found that Withaferin A has a very impressive pharmacological profile especially against cancer and could be useful for the development of the new drug in the future for the treatment of cancer and other metabolic disorders. © 2013 Hainan Medical College.